Biomass index and viscosity values of Moringa oleifera that influenced by Enterococcus faecalis - Cut SORAYA; Zulfan M. ALIBASYAH; Basri A. GANI (Journal of Syiah Kuala Dentistry Society, 2021)
ABSTRACT Enterococcus faecalis (E. faecalis) has been reported as the primary infectious agent in rootcanals. Moringa oleifera (M. oleifera) is said to have the ability to prevent the development of E. faecalis.The purpose of this study was to measure the biomass index and viscosity of the ethanol extract ofMoringa (Moringa oleifera) leaves, which were affected by E. faecalis. This study used Moringa oleiferaand E. faecalis. The biomass index of Moringa oleifera extracts using the Biomass Assay method and theviscosity with the Ostwald Viscometer. The biomass index of M. oleifera affected by E. faecalis at aconcentration of 12.5% for 48 hours was better than other concentrations. CHX has a perfect biomassindex at 24 hours, while at 48 hours, the biomass index increases to close to 10%. Meanwhile, M. oleiferahas a high viscosity at a concentration of 12.5% (0.81 Cp). The results of the viscosity examination werein line with the biomass index with a positive correlation (0.92) and p0.05 between the M. oleiferaconcentrations between the two treatments. M. oleifera has very good biomass and viscosity index at aconcentration of 12.5%. Both are determinants of the development of E. faecalis under the influence of M.oleifera.KEYWORDS bomassa indek, viskositas, E. faecalis